Sino-American Medical Exchange - Ip, MD, Julianne (North American Journal of Medicine and Science, 2009)
The purpose of this article is to offer a template for developing Sino-American medical exchange programs. As globalization is the trend among professions and enterprises, exchange programs in medical education emerge as an ideal vehicle to promote and foster Sino-American relationships and improve world health. Brown University’s Alpert Medical School (AMS) and the Program in Liberal Medical Education (PLME) offers examples of two program templates for developing ongoing Chinese exchange programs. The author believes that three key components are essential for developing and sustaining ongoing exchanges: an interested and devoted faculty member from both countries of the exchange; the support of the highest level of administration at each institution as an exchange involves the waiver of tuition as well as administrative staff necessary to administer the exchange; and funding options to assist in travel, housing and board. Other models of exchange programs will briefly be reviewed as alternative options.